Staphylococcus aureus artificially inoculated in mealworm larvae rearing chain for human consumption: Long-term investigation into survival and toxin production. (December 2022) - Cesaro, Cristiana; Mannozzi, Cinzia; Lepre, Adolfo; Ferrocino, Ilario; Belleggia, Luca; Corsi, Lorenzo; Ruschioni, Sara; Isidoro, Nunzio; Riolo, Paola; Petruzzelli, Annalisa; Savelli, David; Milanović, Vesna; et al.
Graphical abstract: Highlights: S. aureus dynamics in a T. molitor rearing chain for food production were studied. The microbiota of T. molitor eggs was investigated. The results showed that S. aureus was not able to grow during insect rearing. S. aureus was detected in frass from larvae reared on contaminated wheat middlings. Staphylococcal toxins were never detected in any of all analyzed samples. Abstract: The present research reports the results of a long-term study (70 days) of the dynamics of Staphylococcus aureus artificially inoculated in a Tenebrio molitor rearing chain for human consumption. To this end, a rearing substrate consisting of organic wheat middlings was spiked with S. aureus to obtain three initial contamination levels, namely 1 (low level), 5 (medium level) and 7 (high level) Log colony forming unit per gram. Microbial viable counting coupled with metataxonomic analysis were performed to evaluate: i) the persistence and growth of S. aureus in the rearing substrate; ii) the colonization and growth of S. aureus in the insect larvae; iii) the occurrence and load of S. aureus in the frass (excrement from larvae mixed with substrate residues); iv) the presence of S. aureus enterotoxins in the rearing substrate, frass, and larvae. The results of the present study highlighted that wheat middlings contaminated with S. aureus do not represent a suitable environment for the multiplication of the pathogen, irrespective of the initial contamination level. Of note, frass originated from the larvae reared on contaminated wheat middlings might potentially represent a source of S. aureus, with cell loads depending on the initial contamination level. A complex resident microbiota was revealed by metataxonomic analysis. Interestingly, co-occurrence/co-exclusions analysis did not reveal associations between the target microorganism and the microbiota of wheat middlings, larvae, or frass. Considering safety aspects of larvae, the results overall collected suggested that, under the applied conditions, T. molitor represents an inhospitable or even hostile environment for S. aureus, with this latter showing counts below the detection limit in the larvae at the end of the 70-day rearing trial, irrespective of the initial contamination level. The results also suggested that a combination of bactericidal factors, including unfavorable environmental conditions (such as low aw of wheat middlings and frass), might have established in the rearing chain. Finally, the absence of staphylococcal toxins suggests that, even when S. aureus is present at high contamination levels, it is not able to produce toxins in wheat middlings, larvae, or frass.